Socio-Economic Status of Domestic Child Workers - Pokharel, Suman (KMC Research Journal, 2018)
Child labor is one of the serious problems of Nepalese society. This research is carried out with an objective of assessing economic background of the guardians of domestic child workers and to discover the root causes of domestic child workers along with examination of samples on present condition of domestic child workers from Naba Yug Secondary School. This research is carried out by applying descriptive research design. The major finding of the study was majority of the guardians are from poor and agricultural background and most of the child workers spend more hours in domestic works than in their studies.